Method of the Finite-Element Model Formation Containing the 3D Elements for Structural Calculations of the Reinforced Concrete Structures Considering the Crack Opening - Sergei N. Nazarenko; Galina A. Grudcina (Communications - Scientific letters of the University of Zilina, 2021)
This article presents the 3D computational modeling method for reinforced concrete structures. An example of calculation of the reinforced concrete beam, using the Finite Element Method in SCAD++ following proposed algorithm, is given. Results comparison to the analytical calculation of the model with selected reinforcement is presented. For concrete, the 3D solid Finite Elements are used and the 3D beam elements for reinforcement. The model is formed using AutoCAD and AutoLISP, which creates a text data file in SCAD format for the description of model. In addition, computation of the 3D model of the crossbar with a crack is performed. Crack sizes are set in the stretched zone based on data from initial calculation. Graphic results obtained in SCAD++ are presented.